Basophils and Mast Cells Methods and Protocols - Gibbs, Bernhard F.; Falcone, Franco H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
In Basophils and Mast Cells: Methods and Protocols, experts in this challenging field explore techniques to research these cells from the most practical point of view. Given the tremendous influence of mast cells and blood-borne basophils over immune system function, this volume intends to aid the reader in the development of better tools for the isolation of these cells from primary tissues, peripheral blood, bone marrow, or cord blood. Also covered are protocols for the in vitro and in vivo study of their functions. Written in the highly successful Methods in Molecular Biology format, chapters in this book contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls straight from the researchers who use the methods most. Authoritative and easy to use, Basophils and Mast Cells: Methods and Protocols will provide the necessary tools for future research into mast cells and basophils with the goal of aiding in the quest to shed more light on these fascinating cell types.
Paradigm Shifts in Mast Cell and Basophil Biology and Function: An Emerging View of Immune Regulation in Health and Disease -- Purification of Basophils from Peripheral Human Blood -- Mast Cell Purification Protocols -- Generation of a Human Allergic Mast Cell Phenotype from CD133+ Stem Cells -- Generation of Mast Cells from Murine Stem Cell Progenitors -- Integration of the Human Dermal Mast Cell into the Organotypic Coculture Skin Model -- The Absolute Basophil Count -- Detection of Mast Cells and Basophils by Immunohistochemistry -- Mast Cell and Basophil Cell Lines: A Compendium -- Measuring Histamine and Cytokine Release from Basophils and Mast Cells -- Flow Cytometric Allergy Diagnosis: Basophil Activation Techniques -- Microscopy Assays for Evaluation of Mast Cell Migration and Chemotaxis -- Use of Humanized Rat Basophil Leukaemia (RBL) Reporter Systems for Detection of Allergen-Specific IgE Sensitization in Human Serum -- Gene Silencing Approaches in Mast Cells and Primary Human Basophils -- Basophil Stimulation and Signaling Pathways -- Identification and Immunophenotypic Characterization of Normal and Pathological Mast Cells -- Identification of Murine Basophils by Flow Cytometry and Histology -- Mast Cell Mediated Reactions In Vivo.
Keywords: Immunology; Immunology